KESESUAIAN LAHAN BEKAS KEBAKARAN HUTAN SEBAGAI UPAYA KONSERVASI LAHAN DI GUNUNG PANDERMAN RPH ORO-ORO OMBO BKPH PUJON KPH MALANG - Rahayu, Nandang (Jurnal Gamma, 2011)
Nandang RahayuStaf Pengajar Jurusan Kehutanan, Fakultas Pertanian-Peternakan , Universitas Muhammadiyah MalangAlamat Korespondensi : Jl. Raya Tlogomas 246 MalangEmail : nandang21@yahoo.comABSTRACTThis research aim to determine function of area of forest and type of crop matching with farmof ex- forest fire. Land ground used in this research is obtained from farm of Mount of Pandermanof check 227 Malang RPH Oro-Oro Ombo BKPH Pujon KPH.This Research executed at month, moon of June 2011. Data obtained to be calculated andreconciled with standart (measuring rod) is made available, way of this used for determination offunction of area of forest and determination type of appropriate crop. Perception conducted to landground drainage, floods danger, pH land ground, effective deepness, salinitas, tekstur land;ground,ramp, dry month, rainfall of per year, mean of annual temperature and mount erosion danger.Result of this research indicate that region of ex- fire of Mount of Panderman own ramp 45%,type of land ground andosol, intensity of rain 14,73 mm/rainday, drainage of land ground, danger oflight floods, pH of land ground 5,7, salinitas 0,03 mmhos/cm, tekstur land ground of dusty clay,effective deepness 120 cm, dry month (< 75 mm) 6, pouring rain/year 1390 mm, mean of annualtemperature 23,47 0C and mount danger of erosion. From data is above region of ex- fire Mount ofmade compatible Panderman and defended as protected forest (PF) with crop of acacia and bamboo.Keyword : Analyse according to farm, farm of ex- fire.